2018
DOI: 10.1021/acs.energyfuels.8b00232
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Bimolecular Reaction in a Two-Component Fluid under Pyrolytic Conditions: In Situ Probing of the Pyrolysis of Jet Fuel Surrogates Using a Supersonic Expansion Molecular Beam Mass Spectrometer

Abstract: In situ mass spectrometry is demonstrated as a technique to study the pyrolysis of neat fluids at supercritical conditions. These fluids included pure hexane, benzene, and binary mixtures of the two, which were sampled in a supersonic expansion to cool and trap reactants, intermediates, and products in a molecular beam. To identify the reacting species, the molecular beam was subjected to electron impact ionization prior to analysis in a quadrupole mass filter. In addition to the previously reported gas-phase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 56 publications
1
23
1
Order By: Relevance
“…Based on the results of our previous and current study, the chemical structures of substituted aromatics clearly differ when they are synthesized by catalysis versus high-temperature pyrolysis in the absence of a catalyst. In the former case, we have recorded the in situ CID spectra of m / z = 120 species, which can only be explained by a mixture that contains alkyl chain-substituted benzenes.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…Based on the results of our previous and current study, the chemical structures of substituted aromatics clearly differ when they are synthesized by catalysis versus high-temperature pyrolysis in the absence of a catalyst. In the former case, we have recorded the in situ CID spectra of m / z = 120 species, which can only be explained by a mixture that contains alkyl chain-substituted benzenes.…”
Section: Discussionmentioning
confidence: 76%
“…Further evidence that β C–C alkyl bonds do not survive as easily as α C–C alkyl bonds under the extreme temperature conditions comes from our previous study, which probed the pyrolysis of a neat binary mixture of benzene and hexane. In this example, we observed the enhanced production of biphenyl, which was attributed to the lower threshold for phenyl radical production via H-atom abstraction by alkyl radicals in the mixture (3.7–4.3 eV) when compared to direct benzene C–H fission (4.9 eV).…”
Section: Results and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…In Figure , a diagram of the instrument is given, which shows the supercritical pyrolysis source and the two mass spectrometers. In our previous studies, , we demonstrated the single quadrupole mass analyzer combined with 10 eV EI ionization to interrogate the molecular beam formed from the pyrolysis source. In this setup, the ions that are generated by EI are turned 90° into a quadrupole mass filter, which is scanned at a rate of 0.53 amu/ms.…”
Section: Methodsmentioning
confidence: 99%
“…Mass spectrometry is an alternative analytical method to optical spectrometry and is well suited for detailed chemical analysis of in situ pyrolysis reactions because species can be distinguished by their mass-to-charge ratios (m/z) with unit mass resolution using conventional quadrupole mass analyzers. Previously, we have shown that pyrolysis intermediates and products of neat fluids (n-hexane, cyclohexane, n-dodecane, and decalin), 16 binary mixtures (hexane and benzene), 17 and real fuels (Jet A) 16 can be interrogated by forming a supersonic expansion of the reacting fluid into the gas phase. The advantage of our approach when compared to standard analytical methods (e.g., LC-MS, GC-MS, etc.)…”
Section: Introductionmentioning
confidence: 99%